A dendritic Sb2Se3/In2S3 heterojunction nanorod array photocathode decorated with a MoSx catalyst for efficient solar hydrogen evolution. Issue 44 (2nd November 2020) - Liu, Chang; Liu, Tao; Li, Yingzheng; Zhao, Ziqi; Zhou, Dinghua; Li, Wenlong; Zhao, Yilong; Yang, Hao; Sun, Licheng; Li, Fusheng; Li, Zhiqiang
Abstract : Sb2 Se3 nanorod arrays were modified with an n-type In2 S3 layer and a layer of molybdenum sulfide catalyst to form p–n heterojunction photocathodes. A photocurrent of −27 mA cm −2 with a solar-to-hydrogen conversion efficiency of 2.6% can be obtained. Abstract : Developing cost-effective photocathodes that show desirable performance for use in commercial photoelectrochemical water splitting devices remains a fundamental and practical challenge. Sb2 Se3 semiconductors satisfy most of the demands expected for an ideal highly efficient photocathode, including favorable cost and optoelectronic properties. Herein, we have demonstrated outstanding photoelectrodes using a noble-metal-free catalyst, namely, a MoS x -decorated low-cost Sb2 Se3 /In2 S3 heterojunction, as the photocathode. This enabled a maximum photocurrent density of up to −27 mA cm −2 (0 V vs. RHE, 100 mW cm −2, AM 1.5G filter) with a remarkable half solar-to-hydrogen conversion efficiency (STH) of 2.6%, obtained via decreasing charge recombination and accelerating charge transfer through morphological optimization of the In2 S3 layer.